Mitigating self-discharge and improving the performance of Mg–S battery in Mg[B(hfip)4]2 electrolyte with a protective interlayer. Issue 44 (5th November 2021) - Bosubabu, Dasari; Li, Zhenyou; Meng, Zhen; Wang, Li-Ping; Fichtner, Maximilian; Zhao-Karger, Zhirong
Abstract : The self-discharge of magnesium–sulfur battery is improved by adopting interlayer strategy which can effectively absorb dissolved polysulfide, and further improves the electrochemical performance of battery predominantly in Mg[B(hfip)4]2 electrolyte. Abstract : Magnesium–sulfur (Mg–S) battery is receiving much research attention because of its high theoretical energy density, low-cost and sustainable electrode materials. However, the major issues such as self-discharge, low sulfur utilization in cathode and magnesium anode passivation severely hamper the battery operation. In this study, spontaneous magnesium polysulfide formation is observed in the Mg[B(hfip)4 ]2, Mg(TFSI)2 –MgCl2 electrolytes, which leads to severe self-discharge of Mg–S cells. Interestingly, unlike in lithium–sulfur battery, these magnesium polysulfides forms as crystalline magnesium polysulfide on the magnesium foil, which could escalate the self-discharge of the cells. The incorporation of graphene–polyaniline coated carbon cloth (GPN–PANI@CC) as a protective interlayer which effectively adsorbs the polysulfide and inhibit the self-discharge of Mg–S cells in the non-corrosive Mg[B(hfip)4 ]2 electrolyte. This interlayer not only improve the polysulfide retention in cathode but also the capacity values in Mg[B(hfip)4 ]2 electrolyte compared to Mg(TFSI)2 –MgCl2 electrolyte. The cells with interlayer show the initial capacity of 1121 mA h g −1 and maintained a capacity of 500 mA h g −1 after 150 cycles with coulombic efficiency of >99%. This cell design strategy provides a promising approach for improving metal–sulfur batteries.